Peran Gereja dalam Pemerintahan Sejarah Tentang Agama Kristen - Jeni Murni Gulo; Arismawati Halawa; Malik Bambangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This Abstract Outlines The Historical Role Of The Christian Church In Governance, Especially In The Western World. From Its Early Development, The Church Wielded Considerable Influence Over Social And Political Affairs, Particularly After Christianity Became The Official Religion Of The Roman Empire In The 4th Century. Beyond Its Religious Duties, The Church Served As A Powerful Social, Moral, And Legal Authority In Medieval Europe. Through Canon Law, It Governed Various Facets Of Societal Life, Including Marriage, Inheritance, And Social Norms, And Validated The Power Of Rulers Through The “Divine Right” Doctrine. However, The Protestant Reformation Of The 16th Century Marked A Major Shift, Promoting A Separation Of Church And State That Influenced The Rise Of Secular Governance Systems. The Protestant Church Championed Religious Freedom And Individual Autonomy, Foundations For Modern Pluralism And Democracy. In The Contemporary Era, While The Church’s Formal Governance Role Has Declined, It Remains A Moral Voice, Particularly On Social Issues, Justice, And Human Rights. This Study Concludes That The Church's Role In Governance Has Evolved From A Political And Legal Authority To A More Inclusive Moral And Social Role In A Progressively Secular Society.